2015
DOI: 10.1002/adma.201502917
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Moderate‐Refractive‐Index Cu2O Nanospheres as Visible‐Region Nanoantennas with Electromagnetic Resonance and Directional Light‐Scattering Properties

Abstract: Moderate-refractive-index dielectric nano-spheres are found to possess strong electric and magnetic dipole resonances in the visible region. Owing to the overlap of the electric and magnetic dipole resonances, moderate-refractive-index dielectric nanospheres exhibit directional forward scattering at the strongest scattering peak. Such directional scattering is experimentally observed on colloidal Cu2O nanospheres, which are readily prepared through wet-chemistry methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
124
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 41 publications
6
124
0
Order By: Relevance
“…16,26 Designing nanoparticle geometry, one can obtain spectral overlap of electric and magnetic dipole resonances. 27 There is a number of studies that suggest using nanoparticles with more complex shape, such as disks 26, [28][29][30][31] or cubes 32 , or moderate refractive index 33 to decrease backscattering in a broad spectral range. Alternatively, high reflection between the resonances can be utilized for developing a perfect reflector based on all-dielectric metasurface (for near-infrared range designs see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…16,26 Designing nanoparticle geometry, one can obtain spectral overlap of electric and magnetic dipole resonances. 27 There is a number of studies that suggest using nanoparticles with more complex shape, such as disks 26, [28][29][30][31] or cubes 32 , or moderate refractive index 33 to decrease backscattering in a broad spectral range. Alternatively, high reflection between the resonances can be utilized for developing a perfect reflector based on all-dielectric metasurface (for near-infrared range designs see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since most dielectric materials show extremely low values for the imaginary part of refractive index in the visible region, dielectric nanoparticles suffer from much lower losses and heating than their plasmonic counterparts. Many interesting optical functionalities that have been observed with plasmonic nanoparticles can find new insights and breakthroughs by use of dielectric nanoparticles as building blocks, such as structural coloring, directional light scattering, optical chirality, surface‐enhanced spectroscopies, light‐matter strong coupling, and multifunctional metasurfaces …”
mentioning
confidence: 99%
“…In particular, the fabrication of patterns of dielectric nanomaterials by electron‐beam lithography is more complicated than that of plasmonic nanomaterials, since the deposition of thin films of dielectric materials on substrates usually requires chemical vapor deposition, atomic layer deposition and other techniques. Only a few studies have so far demonstrated the chemical synthesis of monodisperse dielectric nanoparticles, including silicon, titania, and cuprous oxide . In addition, chemical vapor deposition and aerosol spray have also been developed for the preparation of dielectric sub‐micrometer spheres with broad size distributions .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From all possible dielectric nanoparticles, spherical ones are specially well-suited to be used as nanoresonators, given their ease of synthesis by either chemical or physical methods and the fact that Mie theory [14] explicitly provides the scattering efficiency of a sphere as a function of the incident wavelength, the sphere's radius and its relative refractive index with respect to that of the surrounding medium. Hence, different arrangements have been proposed for purposes of sensing [15,16] and directional control of scattered radiation [17][18][19][20][21] that are based on the selective excitation of resonances at dielectric nanospheres. In most of these proposals, the obtained scattering response is mainly dominated by dipole resonances, which are those with the lowest energy.…”
Section: Introductionmentioning
confidence: 99%